Impact of Sarcopenia on Survival in Patients Undergoing Living Donor Liver Transplantation. Issue 6 (19th April 2013) - Kaido, T.; Ogawa, K.; Fujimoto, Y.; Ogura, Y.; Hata, K.; Ito, T.; Tomiyama, K.; Yagi, S.; Mori, A.; Uemoto, S.
Abstract Skeletal muscle depletion, referred to as sarcopenia, predicts morbidity and mortality in patients undergoing digestive surgery. However, the impact on liver transplantation is unclear. The present study investigated the impact of sarcopenia on patients undergoing living donor liver transplantation (LDLT). Sarcopenia was assessed by a body composition analyzer in 124 adult patients undergoing LDLT between February 2008 and April 2012. The correlation of sarcopenia with other patient factors and the impact of sarcopenia on survival after LDLT were analyzed. The median ratio of preoperative skeletal muscle mass was 92% (range, 67–130%) of the standard mass. Preoperative skeletal muscle mass was significantly correlated with the branched‐chain amino acids to tyrosine ratio (r = −0.254, p = 0.005) and body cell mass (r = 0.636, p < 0.001). The overall survival rate in patients with low skeletal muscle mass was significantly lower than in patients with normal/high skeletal muscle mass (p < 0.001). Perioperative nutritional therapy significantly increased overall survival in patients with low skeletal muscle mass (p = 0.009). Multivariate analysis showed that low skeletal muscle mass was an independent risk factor for death after transplantation. In conclusion, sarcopenia was closely involved with posttransplant mortality in patients undergoing LDLT. Perioperative nutritional therapy significantly improved overall survival in patients with sarcopenia.